Empowering of Micro, Small and Medium Enterprise (MSMEs) Through Business Legality Assistance and Halal Certivication in Sungai Duren Village: - - Nur Fitri Martaliah; Annisa Indri Meithara; Amalia Rahayu; Putri Anelisa; Ikna Nur Hikmah; Siti Nabila Lisanda (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This community service is part of the SDGs volunteer program converted into a community-based service (KKN) by UIN Sulthan Thaha Saifuddin Jambi. The activity took place in Sungai Duren Village and aimed to empower local MSMEs (Micro, Small, and Medium Enterprises) through licensing assistance and halal certification training. Many MSMEs lacked essential legal documents such as NIB (Business Identification Number), PIRT (Home Industry Food Certificate), and Halal Certification. The program included data collection, administrative mentoring, coordination with relevant institutions, and a focused training session on the halal certification process. The activity resulted in improved legal awareness and compliance among MSME actors, with several obtaining NIB and initiating the process for PIRT and halal certificates.